2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2018
DOI: 10.1109/cvprw.2018.00097
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Face Identification Network Enhanced by Facial Attributes Prediction

Abstract: In this paper, we propose a new deep framework which predicts facial attributes and leverage it as a soft modality to improve face identification performance. Our model is an end to end framework which consists of a convolutional neural network (CNN) whose output is fanned out into two separate branches; the first branch predicts facial attributes while the second branch identifies face images. Contrary to the existing multi-task methods which only use a shared CNN feature space to train these two tasks jointl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Traditional face DeId methods, like blurring or pixelation, are commonly used to prevent observers from recognizing the original identity in an image [30,40]. By analyzing the performance of face identity recognizer, Oh et al [36] showed that the commonly used DeId methods are insecure, especially that the recent deep recognizers can achieve high face re-identification rates [9,33,49]. Alternatively, Newton et al [35] proposed a k-Same algorithm to synthesize de-identified face images for k-anonymized privacy protection [48].…”
Section: Related Workmentioning
confidence: 99%
“…Traditional face DeId methods, like blurring or pixelation, are commonly used to prevent observers from recognizing the original identity in an image [30,40]. By analyzing the performance of face identity recognizer, Oh et al [36] showed that the commonly used DeId methods are insecure, especially that the recent deep recognizers can achieve high face re-identification rates [9,33,49]. Alternatively, Newton et al [35] proposed a k-Same algorithm to synthesize de-identified face images for k-anonymized privacy protection [48].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, deep learning models have performed tremendously in a large range of applications like biometrics [10,11], security [12,13], autonomous vehicle control systems and Spam Filtering. However these models are more susceptible to manipulated input data which is called adversarial examples.…”
Section: A Adversarial Attacksmentioning
confidence: 99%
“…In addition, facial attributes have been taken as auxiliary and complementary information for many facerelated tasks, such as face recognition [57,91,112], face detection [86], and facial landmark localization [139]. Kumar et al [57] first introduce the concept of 'attribute' to facilitate face verification by compact visual descriptions and low-level attribute features.…”
Section: Algorithmsmentioning
confidence: 99%